Tingkat Kemutakhiran Literatur Rujukan Dalam Artikel Ilmiah Pada Jurnal Online Mahasiswa (JOM) Bidang Keperawatan Universitas Riau Publikasi Tahun 2019-2021 - Khusnun Nadhifah; Thamrin Hasan (Perpustakaan Universitas Riau, 2022)
This study aims to determine and describe the level of up-to-date reference literature used in writing scientific articles in the Student Online Journal (JOM). This study examines four aspects relating to the use of reference literature in writing scientific articles resulting from student research published in student online journals, namely: 1) Aspects of up-to-date reference literature, 2) Types of referenced literature, 3) Proportion of language of referenced literature, and 4) Comparison between electronic literature and printed literature. This study uses a descriptive method with the type of study in the form of an analysis of the level of up-to-date reference literature. Data collection is done by taking an inventory and documenting the title of the article, then recording the entire bibliography used as a source or reference. The population and samples used in this study are all scientific articles that have been published on JOM, as many as 93 articles consisting of 1823 reference sources contained in JOM published for the period 2019-2021. The results showed that 1) the latest literature referred to in student online journals amounted to 86.88%. In other words, about 13.12% of other literature references are outdated. 2) The type of reference literature source with the largest number is reference literature originating from primary literature, which is 89.08% and references from secondary literature which are 10.92%. 3) The proportion of literature reference languages ​​that use Indonesian is 83.43% while in foreign languages ​​it is 16.57%. 4) The comparison between literature sourced from electronic and non-electronic (printed) shows a difference of 28'03% who uses printed sources and 71.97% who uses reference sources from electronic library materials. used as a reference by students in supporting the concepts and theories used in writing scientific articles that are in accordance with the criteria for scientific writing.